The Impact of digitalization in supporting the performance of circular economy: A case study of Greece - Stavros Kalogiannidis; Dimitrios Kalfas; Fotios Chatzitheodoridis; Stamatis Kontsas (Journal of Risk and Financial Management, 2022)
Digitalization has the potential to hasten the economic transition towards a more resource-efficient as well as robust circular production system. However, there is a paucity of empirical research on the influence that digitalization has on the ability of a circular economy to function effectively. The objective of this study was to investigate the effect that digitalization has on the performance of the circular economy. The research was based on an empirical analysis of quantitative data obtained from a sample size of 200 investors and entrepreneurs in the financial sector of Kozani, Greece. Regression results showed that there is a positive relationship between digital practices and performance of a circular economy, and that digital business innovations have a positive effect on performance of a circular economy. Even while a sizeable proportion of Greek companies apply new business innovations to support the strategy of resource efficiency, it is abundantly obvious that this percentage is far higher among industrial organizations that place a heavy focus on digitalization. According to the findings of the research, there is a favorable correlation between the adoption of digital business practices and innovations and the success of circular economies. This demonstrates very clearly that digitalization has the potential to function as a driving force behind the development of circular business models.
Keywords: 650; circular economy; digital innovations; digitalization; product– service systems; resource efficiency